#TITLE_ALTERNATIVE# - TAUFIK BUGRAHA (NIM 12804013), MOCHAMAD
A flood within an area can be caused not only by ecosystem degradation and unmanaged environment aspects, but also by meteorological factors especially maximum rainfall. Drainage repair is a mean of reducing the impacts of floods that can be done by analyzing the characteristics of maximum rainfall in the mentioned area. Rainfall frequency analysis is a procedure to estimate the frequency of maximum rainfall plan by implementing the frequency distribution. Log-Pearson III distribution is the chosen frequency distribution according to the Chi-Square test and is considered to represent maximum rainfall data spreading. To calculate the intensity of the rainfall, Van Breen method with the Talbot equation is used for the ITN intersection area, and the Rational Method the method chosen in determining debit plan. The comparison of drainage debit and the planned debit shows the capacity of existing area around ITN intersection, located at Jalan Sumbersari and Jalan Veteran, cannot accommodate the planned debit for a number of periods. That fact is used as a reason to make a plan to repair the physical condition and the geometric of the existing drainage by using the best hydrolysis measurement.